Iri dalam Relasi Sosial - Faturochman, - (Faculty of Psychology, Universitas Gadjah Mada, 2005)
Envy is not a new concept but psychologically has not been studiedintensively. As a preliminary study, this research describes five basic data on the meaning, experience, time, subject, and coping of envyamong university students. The findings show that respondents met difficulties to define envy, however, they had experiences envy towardfriends and relatives. Respondents showed many positive startegies to cope with envy that can reduce the potential problems in their socialrelations.